Evaluación del desarrollo turístico en la comunidad quilotoa –parroquia Zumbahua provincia de Cotopax. - García Laje, Rosa Ingrid (2015)
Evaluation of plans, projects and tourism development programs are inefficient due to insufficient resources or insufficient coordination of responsibilities, causing waste of human talent, opportunities for tourism development and the improvement of the human condition. Here arises the need to "Evaluate the tourist development in the Quilotoa - parish Zumbahua province of Cotopaxi community." The main objective is to identify and evaluate the implementation of programmes or projects of tourism development for the community, presented by public or private institutions during the period 2005 to 2014. In the methodology applied six indices of evaluation ex post the Manual of formulation, evaluation and monitoring of projects of Ernesto Cohen according to the Economic Commission for Latin America and the Caribbean (CEPAL), resulting in existence three and development plans tourism, where the plan with less progress of projects was the tourism management plan strategic tourism development plan obtained greater compliance with their projects.In the methodology applied six indices of evaluation ex post the Manual of formulation, evaluation and monitoring of projects of Ernesto Cohen according to the Economic Commission for Latin America and the Caribbean (CEPAL), resulting in existence three and development plans tourism, where the plan with less progress of projects was the tourism management plan strategic tourism development plan obtained greater compliance with their projects.